Assessing the financial aptitude of industrial firms to implement servitised earnings models. (26th February 2020) - Kamp, Bart
Servitisation research covers a large variety of aspects related to novel earning models, like pay-per-use schemes or other outcome-oriented charging modalities. However, it may overlook aspects related to bookkeeping and financing such operations. This article introduces the concept of financial aptitude to hypothesise under which circumstances industrial firms are likely to introduce servitised earnings models. It builds upon insights from management reporting and financialisation theories for that purpose. It postulates that activity-based cost accounting and interaction with organisations that specialise in the financing and/or managing of industrial assets raises the propensity to take up servitised earnings models.